Gender discrimination in societal and familial realms: Understanding agency among Chinese marriage migrant women in Switzerland. (March 2021) - Chen, Yali
To understand the agency of Chinese marriage migrant women in Switzerland in their everyday life, the present article examines the reasons why Chinese women marry European men and their post-migratory life in Switzerland. Based on interviews with Chinese marriage migrant women, the article discusses their gendered representations before migration (as "leftover women" or "divorced women") to being "foreign wives" after migration to Switzerland. Their migration from China to Switzerland also resulted to a change in their roles from "professional women" to "homemakers." The gender-related discrimination the women encountered from China to their post-migration life in Switzerland demonstrates a continuum of gender discrimination in which they highly exert their agency that has also been enhanced by acts of resistance.